Long-Term Outcome of Mitochondrial Diseases - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The clinical spectrum and long-term outcome of 73 children diagnosed with mitochondrial diseases between 1985 and 2005 were investigated at the Universities of Montreal and Toronto, Canada.